An Enhancement of RTS/CTS Control Handshake in CSMA/CA Based MAC Protocol for an Efficient Packet Delivery over Multihop Wireless Mesh Network (WMN) - Gannapathy, Vigneswara Rao; Tuani Ibrahim, Ahamed Fayeez; Zakaria, Zahriladha; Othman, Abdul Rani; Abdul Latiff, Anas (Sun Publications, 2013)
The Carrier Sense Multiple Access with Collision Avoidance (CSMA/CA) based Medium Access Control (MAC) protocol uses a short request-to-send (RTS) and clear-to-send (CTS) control packets prior of actual data packet transmission. The function of the CSMA/CA based MAC protocol in wireless communication is to facilitate wireless nodes (i.e. laptop, PC, smart phones and etc) to access a wireless medium efficiently. Besides, it is also efficiently manage the wireless medium when more wireless nodes involving in transmission activity in the network. This protocol allows all wireless nodes in the network to communicate between each other without collision. Since collisions may only occurred on the RTS control packets thus it can reduce the actual data collision on the medium. The RTS/CTS control handshake provides better performance and reduce the duration of collision especially when long data packets are transmitted over wireless medium. However, even though the CSMA/CA based MAC protocol working effectively and provides better throughput performance over single hop communication but it performance degrade significantly when directly applied in multihop Wireless Mesh Network (WMN). The reason behind this poor performance is due to the inefficient packet delivery of CSMA/CA based MAC protocol in multihop network. The exchange of RTS and CTS signaling that required at each hop throughout the multihop network eventually will cause the large overheads and subsequently degrade network throughput. Therefore, in this paper, an enhancement of RTS/CTS handshake has been proposed in order reduces the signaling overheads and ultimately allows a smooth packet delivery in the multihop network without any collision. In this work, the multihop network performances are evaluated analytically in terms of throughput and overhead. It is proven that the new method of RTS/CTS handshake provides significant improvement in throughput and overhead.